It takes two to transport via an elevator - Byrne,B (Cell Research, 2021)
Membrane transporter proteins are critical for cellular uptake and export of molecules, and are reported to function by a number of different molecular mechanisms. The new occluded state structure of the uracil transporter, UraA, from Escherichia coli, reveals that both coordinated movement of the two domains of a single protomer together with dimer formation are important for transport activity.